2021
DOI: 10.1021/acsnano.1c04835
|View full text |Cite
|
Sign up to set email alerts
|

Surface Topography of Polyethylene Glycol Shell Nanoparticles Formed from Bottlebrush Block Copolymers Controls Interactions with Proteins and Cells

Abstract: Although poly­(ethylene glycol) (PEG) is commonly used in nanoparticle design, the impact of surface topography on nanoparticle performance in biomedical applications has received little attention, despite showing significant promise in the study of inorganic nanoparticles. Control of the surface topography of polymeric nanoparticles is a formidable challenge due to the limited conformational control of linear polymers that form the nanoparticle surface. In this work, we establish a straightforward method to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…This suggests the micelles have reached a steady state. Recent theoretical and experimental work has shown that the side chain length asymmetry of the two blocks can impact micelle morphology, aggregation number, and surface roughness due to packing frustration at the core–corona interface. We hypothesize that the additional free energy contribution of side chain crowding near the core–corona interface creates at least two local minima in free energy–micelle size space that are separated by a significant energy barrier, thus leading to a bimodal micelle size distribution.…”
mentioning
confidence: 95%
“…This suggests the micelles have reached a steady state. Recent theoretical and experimental work has shown that the side chain length asymmetry of the two blocks can impact micelle morphology, aggregation number, and surface roughness due to packing frustration at the core–corona interface. We hypothesize that the additional free energy contribution of side chain crowding near the core–corona interface creates at least two local minima in free energy–micelle size space that are separated by a significant energy barrier, thus leading to a bimodal micelle size distribution.…”
mentioning
confidence: 95%
“…The topography was found to influence both cellular uptake and protein adsorption. Adapted with permission from Grundler et al 152 Copyright 2021. American Chemical Society.…”
Section: Theranostics and Multifunctional Carriersmentioning
confidence: 99%
“…10B). 152 In altering the amphiphile dimensions, including brush width, block length and interfacial asymmetry, the team was able to produce micelles with differing amphiphile packing densities that resulted in nanoparticles with spiky topography in their shells. With the influence of protein adsorption on nanomaterial behaviour in biological systems becoming more evident, the various micelles were further analysed for their ability to prevent bovine serum albumin (BSA) adsorption.…”
Section: Structure–function–property Relationship Investigationsmentioning
confidence: 99%
“…Nanoparticles (NPs) are widely recognized as important starting materials in nanotechnology due to their unique properties, such as reactivity, electrical conductivity, , mechanical strength, , magnetic susceptibility, and biological interactions. Thus, NPs have shown great potential in various fields including sensing, energy storage, and biological imaging. However, their small size results in high surface energy, which can result in NPs tending to aggregate and negatively affect the stability and function of the product, especially in paints, inks, and related materials. Therefore, controlling the interfaces and interactions of NPs is crucial for their successful applications in engineered nanomaterials, optics, catalysis, and nanomedicine. …”
Section: Introductionmentioning
confidence: 99%